Influence of coastal alluvial aquifer on groundwater chemistry in Wates, Yogyakarta, Indonesia. Issue 1 (1st August 2022) - Thin, P P; Hendrayana, H; Kawasaki, S
Abstract: Saline groundwater is found far from the coastline, whereas closer groundwater has low salinity in the Wates area, Indonesia. This situation which has led to problems linked to the coastal aquifer, shows different groundwater chemistries. This connection needs to highlight the geochemical evolution of aquifers. This research aims to evaluate the hydrochemical characteristics in Wates Sub-District, Kulon Progo District, Indonesia. The study area is located in the southern part of the Kulon Progo with an aquifer of marine and fluvial deposits. The boundary of the south is the Indian Ocean. The approach is based on analyzing the major ions of 27 groundwater samples, and the XRD results include the Stiff diagram and the Stuyfzand classification. The Stiff diagram showed in agreement with that of the Stuyfzand classification. Results showed that the F2-(CaHCO3)2Ø and F1-(NaMix)Ø types reflect the recharge process and dominate the dissolution of silicate minerals. Halite dissolution originates in topographically flat areas of the Bs1-NaCl (-) water. Total hardness is softer than others as a result of cation exchange. The groundwater chemistry's geochemical processes are the dissolution of silicate and halite minerals, ion exchange, and fresh and seawater mixing. This research indicates to focus on pumping problems in the aquifer.